THE ROLE OF MATRA BASTI AND KATI BASTI IN KATISHOOL WITH SPECIAL REFERENCE TO LUMBAR SPONDYLOSIS (AYUSHDHARA, 2017)
The degenerative change in the disc and lumbar spine is known as Lumbar Spondylosis. Katishula is localized Vata vyadhi in which Prakupita vayu affects Sandhi. According to Anshansha Kalpana of Katishula, the Vata vitiated due to Ruksha and Shita guna, which lead to Dhatukshaya. Katishula, according to its sign and symptoms can be compared to Lumbar spondylosis in modern medical science and numbers of Ayurvedic authors also recently have combined Katishula as lumbar spondylosis. Hence, the disease lumbar spondylosis.Thus, to treat the Vyadhi opposing treatment should be done and it should be Snehana, Svedana and Basti. Out of Panchakarmas, Basti Chikitsa is most important as it radically pacifies the morbid Vata, the sole Dosha, responsible for the movements of all Dosha, Dhatu and Mala within the body. It is called as half treatment of Chikitsa which is also called as “Ardha Chikitsa”. The Matra Basti is one of the types of Anuvasana Basti which can be administered to any individual any time. Matrabasti is such a Chikitsa that is applicable in all the Vatavyadhi. Kati basti is one of the dual Panchakarma therapies which have the action of both Snehan and Swedan for Asthisandhigata vata. The symptoms like Katishul, Pidanasahatva, Katigraha, Akunchan Prasaranayoh Shula, Difficulty in forward bending, Anidra were graded from 0 to 4 for assessment. X-ray that determines spondylosis, osteoporosis and spinal degenerative conditions were considered. So for this study Prasarni Giloy tail was used for Kati basti (35mins) along with matra basti (60ml) in Group A and other group B was treated only with Matra basti (60ml). In this study, Basti is given for 9 days. Prasarni giloy Matra Basti & Katibasti i.e., Group A is found to be very much symptomatically effective in patients suffering from Katishula. Overall percentage of relief was more in Group A (72.33%) than Group B (64.33%).